Frank Castorf's Art of Institutional Dis/avowal : A Volksbühne Elegy. Issue 2 (25th April 2018) - Woolf, Brandon
Abstract : There is so much to say about the persistent critiques of and mobilizations against Chris Dercon's vision (or lack thereof) of the newly named Volksbühne Berlin. My task here, however, is a different one: to begin to understand why there has also been such persistent mobilization on behalf of the Volksbühne am Rosa-Luxemburg-Platz. In what follows, I provide some critical context for reflection upon the unique role the Volksbühne played in post-Wall Berlin. I suggest that in his twenty-five-year tenure at the Volksbühne, Frank Castorf worked to refunction the theatre apparatus itself, to transform the theatre as state institution, as interrelated set of supporting structures that extend beyond and behind the proscenium arch. Further, Castorf's work as both director and artistic director helps us to understand the complex relations between a theatre aesthetic, which exposes and critiques the structures of its (state) support, and a theatrical institution with similarly ambitious goals. As an aesthetic and as an infrastructural project, Castorf's Volksbühne enacted a new kind of public theatre in Berlin—and it is this project of institutional dis/avowal that we must remember (and dare to reenact) as so much more than reactionary or provincial nostalgia.